Understanding sustainable consumption in an emerging country: The antecedents and consequences of the ecologically conscious consumer behavior model. (21st December 2018) - Yarimoglu, Emel; Binboga, Gul
Abstract: For past few decades, consumers have lately started to adapt sustainable consumption in emerging countries. The increasing importance of sustainable consumption led the researchers to analyze green purchase and ecological behaviors. The aim of this study was to examine the antecedents of ecologically conscious consumer behavior model and show the relationships among ecologically conscious consumer behavior, green purchase conspicuous behavior, and green purchase intention based on the theory of planned behavior in an emerging country. Data were collected from 650 consumers in Turkey, one of the emerging countries, by using face‐to‐face survey technique and analyzed by factor analyses and structural equation modelling. In findings, environmental concern, altruism, and perceived consumer effectiveness were found as the antecedents of the model, and there were significant effects of ecologically conscious consumer behaviors on green purchase conspicuous behaviors and green purchase intentions.